2018
DOI: 10.3389/fmicb.2018.02588
|View full text |Cite|
|
Sign up to set email alerts
|

Exposure to Antibiotics Affects Saponin Immersion-Induced Immune Stimulation and Shift in Microbial Composition in Zebrafish Larvae

Abstract: In the last decades, pollution of the environment by large scale use of antibiotics in agriculture and human medicine have led to increased antimicrobial resistance in both the environment and the host animal microbiome. Disturbances in the host microbiome can result in impaired immunity and reduced resilience of aquaculture species. Here, we investigated whether environmentally measured levels of the commonly used antibiotics ciprofloxacin and oxytetracycline influences the host microbiome and susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 35 publications
(47 reference statements)
2
33
0
Order By: Relevance
“…After quantifying RNA by a NanoDrop 1000 Spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA), cDNA was generated from 1 μg of RNA using Superscript™ III First Strand Synthesis Systems (Invitrogen, Carlsbad, CA, USA) according to the manufacturer's instructions. The diluted cDNA corresponding to 125 ng of RNA was used as a template for each reaction of quantitative polymerase chain reaction (qPCR) using the ABsolute TM qPCR SYBR® Green Mix (Thermo Fisher Scientific, Waltham, MA, USA) as previously described ( 27 ). The sequences of the primer used in this study can be found in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…After quantifying RNA by a NanoDrop 1000 Spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA), cDNA was generated from 1 μg of RNA using Superscript™ III First Strand Synthesis Systems (Invitrogen, Carlsbad, CA, USA) according to the manufacturer's instructions. The diluted cDNA corresponding to 125 ng of RNA was used as a template for each reaction of quantitative polymerase chain reaction (qPCR) using the ABsolute TM qPCR SYBR® Green Mix (Thermo Fisher Scientific, Waltham, MA, USA) as previously described ( 27 ). The sequences of the primer used in this study can be found in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Tg (mpeg1:mCherry/mpx:eGFPi 114 ) (28,29) and wild-type zebrafish were maintained in Zebtec family tanks (Tecniplast, Buguggiate, Italy) under continuous flow-through at 28 • C (14/10-h light/dark cycle) and fed daily with Tetramin Flakes (Tetra, Melle, Germany). For the experiments using zebrafish larvae, embryos were obtained from the adult transgenic zebrafish by natural spawning and raised with embryo medium (E3) water as described previously (27). OM fucoidan powder (>95% pure fucoidan) extracted from C. okamuranus as described previously (30) was provided by South Product Co., Ltd., Okinawa, Japan.…”
Section: Zebrafish and Fucoidanmentioning
confidence: 99%
See 2 more Smart Citations
“…Although increased expression levels of CD86, TNF-α and IL-1β were observed, the decreased expression of CD206 in macrophages after treatment with ciprofloxacin and MCIP also exerted some tumor-inhibitory effects. However, other studies reported that ciprofloxacin could promote the expression of TNF-α and did not affect the expression of IL-1β in animal models (46). The changes in these cytokines were not consistent with the classical model of LPS-induced M1-like macrophage polarization (47).…”
Section: Discussionmentioning
confidence: 83%